Mediating Effect of Internet Knowledge on The Relationship Between Perceived Usefulness And E-ticketing Adoption of Ethiopian Airlines in Nigeria. - Yusuf, Maryam M.B; Yahaya, Hamma Adama; Abubakar, Adamu magaji; Ago, Amina Usman Sabo (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Airline industries are one of the fastest growing industries in the world. Since the coming of online marketing, it has become one of the important media where airlines ticket is bought and sold. Estimated 60% of Nigerian travellers choose to purchase their Ethiopian Airlines ticket over the counter, where hardcopy paper tickets will be printed out for them. Hence, they do not perceive the usefulness of adopting e-ticketing provided by Ethiopian Airlines. Therefore, this study examined the mediating effect of internet knowledge on the relationship between perceived usefulness and e-ticketing adoption of Ethiopian Airlines in Nigeria. The data were collected through self-administered questionnaires using a random sampling technique from 360 Ethiopian Airlines customers in Nigeria. The questionnaire comprised of four sections measuring internet knowledge, perceived usefulness, and e-ticketing adoption. The last part of the questionnaire captured the respondents’ profiles. The proposed model and research hypotheses were tested using Path Analysis in Structural Equation Modelling (SEM). The findings of the study supported the four proposed hypotheses. In addition, the study discovered that internet knowledge partially mediates the relationship between perceived usefulness and e-ticketing adoption of Ethiopian Airlines in Nigeria. The result of this study contributed theoretically by providing some modifications and new measures for e-ticketing adoption, internet knowledge, and perceived usefulness. The findings also make contributions theoretically by suggesting the use of SEM this could be preserved as the new framework for linking perceived usefulness, internet knowledge, and e-ticketing adoption. These findings may help the passengers of Ethiopian Airlines in Nigeria understand the benefit of adopting Ethiopian Airlines e-ticketing and how the adoption brings ease of life to their daily activities. Since this study also highlights the factors that drive e-ticketing uptake, it will enable the stakeholders to create customized services that fit customers' requirements and aspirations. As a result, Ethiopian Airlines executives should consider the practical implications of these latent characteristics, which are critical in helping Nigeria's economy thrive and improve service quality.